Effect of Fat on Quality Characteristics of Whey obtained from Manufacture of Ricotta Cheese: Effect fat on quality characteristics of whey - Gautam, Avinash Chandra; Goel, Nitika; N, veena; Singh, Pranav Kumar; Kumar, Siva (Indian Journal of Dairy Science, 2024)
The Ricotta cheese whey (RCW) is obtained during the manufacturing of Ricotta cheese as byproduct. It is highly nutritious and can be utilized in the manufacture of whey-based beverages. In the present study, RCW was analyzed for its sensory and physico-chemical properties obtained during the manufacture of Ricotta cheese from mixture of whey to milk (80:20) with different fat levels (0.1%, 1.5%, 3.0% and 4.5%). The results indicated that an increase in the fat content of milk used in the manufacturing of Ricotta cheese has a significant effect on the composition of RCW. The fat content of RCW increased with the increase in the fat content of milk used in the manufacture of Ricotta. The protein content was reported to be highest in the RCW prepared from milk with no-fat. The L* value of the sample increased while a* and b* values of the sample decreased with increase in the fat content of RCW. Sensory results revealed that RCW with higher fat content showed the highest acceptability as compared with the other samples.